Coronary Microvascular Dysfunction in Rheumatoid Arthritis Compared to Diabetes Mellitus and Association With All‐Cause Mortality. Issue 2 (1st February 2021) - Liao, Katherine P.; Huang, Jie; He, Zeling; Cremone, Gabrielle; Lam, Ethan; Hainer, Jon M.; Morgan, Victoria; Bibbo, Courtney; Di Carli, Marcelo
Abstract : Objective: Coronary microvascular dysfunction (CMD) is a predictor of cardiac death in diabetes mellitus (DM) independent of traditional cardiovascular (CV) risk factors. Rheumatoid arthritis (RA) is a chronic inflammatory condition, with excess CV risk compared to the general population, in which CMD is hypothesized to play a role; however, there are limited data on CMD in RA and any association with clinical outcomes. The objective of this study was to compare the prevalence of CMD in RA to that in DM and to test the association with all‐cause mortality. Methods: We performed a retrospective cohort study using data from a registry of all patients undergoing stress myocardial perfusion positron emission tomography as part of routine clinical care from 2006 to 2017. The inclusion criterion was a normal perfusion scan. Patients with RA or DM were classified using previously published approaches. Coronary flow reserve (CFR) was calculated for all patients in the registry and linked with mortality data. CMD was defined as CFR <2.0. Results: We studied 73 patients with RA and 441 patients with DM. Among patients with a normal perfusion scan, the prevalence of CMD in RA was similar to that in DM ( P = 0.2). CMD was associated with increased risk for all‐cause mortality in RA (hazard ratio 2.4 [95% confidence interval 1.4–4.2]) as well as increased risk for cardiac‐related death at rates similar to those in DM. Conclusion: These findings suggest an important role for CMD as a potential contributor to excess CV risk and mortality in RA, as previously observed in DM, as well as evidence for a mechanistic link between inflammation and cardiovascular disease.